Career Self-Management in Small- and Medium-sized Businesses: Strengths and Limitations - Goyer, Liette (Canadian Journal of Counselling and Psychotherapy, 2012)
Using an evaluation framework (Canadian Research Working Group on Evidence-based Practice in Career Development, CRWG, 2007), this study has developed a self-guided career management process. Goyer has tested the process and evaluated its effectiveness among 56 workers employed in businesses. The evaluation assessed four variables: self-efficacy (Michaud, Savard, Leblanc, & Paquette, 2010), quality of career maintenance management (Lamarche, Limoges, Guédon, & Caron, 2006), self-esteem (Lecompte, Corbière, & Laisné, 2006), and career self-management (CRWG, 2009). Effective strategies have emerged from a follow-up interview and from the results of the study. The effects of the process on its users is reviewed followed by critical reflection on the strengths and limitations of providing this type of guidance process in business (Goyer, Hiebert, Borgen, & Savard, 2010).